A dispersive liquid–liquid microextraction method based on the solidification of a floating organic drop combined with HPLC for the determination of lovastatin and simvastatin in rat urine. (June 2014) - Zhao, Longshan; Zhao, Pan; Wang, Linli; Ma, Xiaowei; Hou, Xiaohong; Li, Famei
ABSTRACT A dispersive liquid–liquid microextraction method based on solidification of floating organic drop combined with HPLC was developed for the determination of lovastatin and simvastatin in rat urine for the first time. 1‐Dodecanol and methanol were used as the extraction and disperser solvents, respectively. Several important parameters influencing the micro‐extraction efficiency were studied and systematically optimized, including the type and volume of extraction solvent and disperser solvent, extraction time, pH and salt concentration. The analytes were separated on a Kromasil C18 column at 30°C with a mobile phase of methanol and 0.2% acetic acid in water (83:17, v/v) and detected at 238 nm. Under the optimal conditions, the maximum number of enrichment factors for both analytes was 27. The linear ranges were 20.08–1004 and 20.00–1000 µg/L with the correlation coefficients ranging from 0.9990 to 0.9994 for lovastatin and simvastatin, respectively. The volume of organic solvent consumed in extraction was <0.3 mL, and the extraction time was 10 min. The newly developed environment‐friendly sample pretreatment method will be a good alternative to conventional techniques, such as solid‐phase extraction, liquid–liquid extraction and protein precipitation, for the HPLC determination of lovastatin and simvastatin in biological samples. Copyright © 2014 John Wiley & Sons, Ltd.